Educação Física Escolar: práticas de pesquisa e saberes científicos em revista (1979-2009) - Corte, Rachel Borges (2009)
Aims to understand how were produced and broadcasted the representations presents in the discourses of the scholar Physical Education articulists on research practices and scientific knowledge in the last thirty years (1979-2009), and the representations of the historic process of the scientific thought consttuition of the ground through the employed theory-methodological resources by the researchers. Uses as source the Revista Brasileira de Ciências do Esporte (RBCE) (Brazillian Science of Sports Magazine), chancelled by the Colégio Brasileiro de Ciências do Esporte (CBCE) (Brazillian College of Scienece of Sports). The magazine appropriates itself of the discourses of the called “mother sciences”, aiming to be recognized as scientific authority of the ground. Understood as a strategical device of the senses conformation, the RBCE uses its power to determine what deserves to be broadcasted or/and to be preserved in the scientific área. Analyze the way of circulation of the Physical Education knowledge, its practitioners and practices. Has as theory reference the Chartier (1988) proposals on the representation fights by the scientific authority in an area full of interests and strategies that begins in the specific place of power (CERTEAU, 2007) - the CBCE. Among this author proposals, was also mobilized the notion of appropriation. The methodological basis was supported by the Ginzburg (2003) indiciary paradigm through wich was investigated what was said and not said in the publication. Was observed that studies on school appear fragmented into several issues, with various themes, using the space and its practitioners as a fertile ground for research, indicating that much has been published, but there are few studies that are aimed to pedagogical practice aiming at their reframing. Moreover, concludes that the specific theorizing on Physical Education focuses on the integration of different approaches, setting up a synthesizer theorizing knowledge in the light of the specific needs of educational practice.